Socio-philosophical and economic factors in the search for decent living conditions: The mass migration of people - Muxtarov Utkirjon Mutalibjanovich (Periodica Journal, 2025)
This research is dedicated to analyzing the process of mass human migration in relation to the search for decent living conditions. It elucidates the social, economic, political, and cultural factors of migration, as well as the intensification of migration processes in the context of globalization. The study provides a scientific and theoretical foundation for the impact of internal and external migration on societal development, the labor market, demographic situations, and social stability. Additionally, it explores the philosophical essence of the concept of a decent life and its intrinsic connection with migration processes. The research findings contribute to drawing scientific conclusions for improving migration policies and enhancing the population's standard of living.
Keywords: migration; mass migration; decent living conditions